Geomorphological dynamics of tidal channels and flats in mangrove swamps. (5th February 2022) - Shih, Shang-Shu; Cheng, Ting-Yu
Abstract: The tidal channels and mudflats of estuarine wetlands have vital ecological functions for the habitat of aquatic organisms and the exchange of nutrients and sediment. Understanding the spatiotemporal dynamics of their morphology helps to formulate an appropriate management plan for mangrove swamps. The water levels, wetland topography, suspended sediment concentration, sediment particle size, and mangrove stand characteristics were investigated in the Tanshui River estuary to verify the geomorphological model established in this study. The decoupled model includes a hydrodynamic module, a sediment module, and a mangrove module to integrate the effects of tidal hydroperiods and river currents. The simulation results revealed that the model could effectively predict the tidal channel morphodynamics, but the siltation of tidal mudflats was overestimated. Sensitivity analysis results showed that the soil properties and erosion rate had the highest impacts. The flow velocities and bed shear stress of the tidal channels were several times those of the mudflats. The hydrodynamics of ebb tide were more extensive than those of flood tide. The asymmetry between ebb and flood tides contributes to maintaining a self-sustaining tidal channel. The deposition rate during the flood period was 20–80 times that of the normal period. The results indicated that river floods entrained large amounts of sediment to accelerate wetland siltation. The reduced tidal range scenarios and the corresponding suspended sediment input suggested an alternative for preventing channel deposition in the wetland. This study offers a quantitative tool for delivering effective maintenance of tidal channels and tidal flats that may enhance the integrated and adaptive management of mangrove swamps. Highlights: The geomorphological model contains hydrodynamic property, sediment transport process, and mangrove characteristics. Model simulation results agree with field observations and reveal the prediction capability. River floods induce tens of times to average siltation and cause tidal channels to alter into flats. Ebb tides are critical in removing larger particles of suspended sediments in mangrove swamps. Reduced tidal range and suspended sediment inputs are significant in sustaining wetland geomorphology.